PENERIMAAN PEREMPUAN TERHADAP BOYS LOVE DALAM ALTERNATE UNIVERSE (AU) DI TWITTER - Devi Apriliana; Syafrida Nurrachmi Febriyanti (Cahaya Ilmu Bangsa, 2025)
The phenomenon of boys’ love (BL) in alternate universe (AU) fan fiction on Twitter is experiencing increased popularity among fans. This study aims to analyze women's reception and interpretation of BL AU on Twitter, as well as to explore their views on gender and sexuality. Using a qualitative approach, then analyzed using Stuart Hall's Encoding-Decoding method, data were collected through in-depth interviews with 8 women who had read BL AU on Twitter as informants. The findings of this study reveal that there are differences in the reception of BL AU by women, influenced by factors such as belief, cultural background, and personal values. BL AU is not only an entertainment but also a space for socializing with fellow fans. In addition, Twitter is considered as an easy-to-use platform for reading AU because of its features.